Sosialisasi Pemahaman Laporan Keuangan Dalam Menunjang Usaha Mikro Kecil dan Menengah (UMKM) Melalui Metode Aplikasi Di Kelurahan Alak Kecamatan Alak Kota Kupang - Hermyn Hina; Dedy Raidons Se’u (LP3M IAIFA Kediri, 2022)
The Covid-19 pandemic period that has occurred since February 2020 which has hit the Indonesian nation until now and natural disasters caused by tropical cyclone Seroja that hit East Nusa Tenggara Province including Kupang City from April 3 to 5, 2021, has a bad impact on financial management in an institution or organization that is profit-oriented or non-profit oriented, this is due to the large number of unexpected expenses that affect the financial statements in a company or organization. The results achieved in the PKL Community Service activity